2022
DOI: 10.1186/s10020-022-00594-2
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of pyroptosis-related inflammasome pathway in atherosclerosis

Abstract: Atherosclerosis (AS), a chronic sterile inflammatory disorder, is one of the leading causes of mortality worldwide. The dysfunction and unnatural death of plaque cells, including vascular endothelial cells (VEC), macrophages, and vascular smooth muscle cells (VSMC), are crucial factors in the progression of AS. Pyroptosis was described as a form of cell death at least two decades ago. It is featured by plasma membrane swelling and rupture, cell lysis, and consequent robust release of cytosolic contents and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…After 8 weeks of high-fat diets, mice showed reduced levels of IL-18, caspase-1/11 in the bone marrow, and significantly reduced AS plaques ( Liaqat et al, 2020 ), providing the first solid evidence that NLRP3 inflammasome promotes AS development. Following this observation, Shi et al ( Xu et al, 2022 ) found upregulated levels of NLRP3, ASC, caspase-1, IL-1β, and IL-18 in carotid atherosclerotic plaques from patients undergoing carotid endarterectomy, with unstable plaques expressing higher levels of these compounds as opposed to stable plaques. In contrast, inhibition of the NLRP3 signaling pathway by siRNA interference suppressed pro-inflammatory cytokines in high-fat diet-fed ApoE −/− mice ( Jin et al, 2022 ).…”
Section: Molecular Mechanism Of Anti-as By Glp-1rasmentioning
confidence: 90%
“…After 8 weeks of high-fat diets, mice showed reduced levels of IL-18, caspase-1/11 in the bone marrow, and significantly reduced AS plaques ( Liaqat et al, 2020 ), providing the first solid evidence that NLRP3 inflammasome promotes AS development. Following this observation, Shi et al ( Xu et al, 2022 ) found upregulated levels of NLRP3, ASC, caspase-1, IL-1β, and IL-18 in carotid atherosclerotic plaques from patients undergoing carotid endarterectomy, with unstable plaques expressing higher levels of these compounds as opposed to stable plaques. In contrast, inhibition of the NLRP3 signaling pathway by siRNA interference suppressed pro-inflammatory cytokines in high-fat diet-fed ApoE −/− mice ( Jin et al, 2022 ).…”
Section: Molecular Mechanism Of Anti-as By Glp-1rasmentioning
confidence: 90%
“… 134 , 135 , 136 Many risk factors are involved in the development of atherosclerosis, but the mechanisms are not completely understood. Recent studies have found that multiple risk factors trigger pyroptosis in atherosclerosis associated cells, including endothelial cells (ECs), macrophages, and smooth muscle cells (SMCs), 137 , 138 , 139 , 140 suggesting that pyroptosis plays an important role in the pathological development of atherosclerosis (Figure 3 ).…”
Section: Pyroptosis and Cvdsmentioning
confidence: 99%
“…Indeed, while apoptosis remains the predominant form of macrophage death in atherosclerosis, less-well characterized types of regulated necrosis, such as pyroptosis, necroptosis, parthanatos and ferroptosis have been reported ( 11 , 12 ) ( Figure 1 ). Pyroptosis occurring in response to bacterial infection, is accompanied by NLRP3 inflammasome activation and by maturation of pro-inflammatory cytokines IL-1β and IL-18 ( 13 , 14 ). Necroptosis is a form of cell death activated by death receptors, such as TNFR1, IFNR and TLR3/4 ( 15 ).…”
Section: Atherosclerosis and Macrophage Deathmentioning
confidence: 99%